Socialization of Petanque Sports at SMAS YASPIB Bontolempangan Gowa - Badwi, Adam; Arba', Muhammad Arkanul; Rahmatullah, Wahyu; Rerung, Charmila Tandi; Aulria, Siti Nurhalizah Mutia; Arga, Arga; Hasran, Hasran (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2025)
The socialization of petanque sport at SMAS YASPIB Bontolempangan Gowa aims to introduce and develop students' interest in petanque as an alternative physical activity that can improve physical and mental fitness. This activity provides a platform for students to learn the basic techniques of petanque, understand game rules, improve hand-eye coordination, develop game strategies, and build sportsmanship and teamwork character. Through this socialization, it is hoped that students can develop interest in non- conventional sports, increase daily physical activities, build self-confidence, and create a positive sports culture in the school environment.